Botulinum toxin in the treatment of neuralgia and neuropathic pain - Mielniczek, Katarzyna (Journal of Education, Health and Sport, 2021)
Introduction: Botulinum toxin is one of the most powerful neurotoxins currently known, with high affinity to the cholinergic synapse, which sufficiently inhibits the release of acetylcholine. Its use has proved to be effective in the treatment of many diseases of the musculoskeletal system. Although most of the therapeutic effects of botulinum toxin are due to the temporary relaxation of skeletal muscles (caused by inhibition of acetylcholine release), research is ongoing into its effects on the nervous system. Purpose of the work: The aim of the study is to analyze the effectiveness of botulinum toxin in the treatment of neuralgia and neuropathic pain. Method: The relevant samples were accessed by means of an electronic search in the PubMed database. The analysis used reviews and meta-analyzes posted on the platform over the last 10 years. Conclusions: Botulinum toxin has great potential in the treatment of pain. It is multitasking due to its favorable safety profile and long-lasting relief from a single injection compared to other pain medications. The side effects caused by it were assessed to be mild to moderate and included a local skin reaction (swelling), injection site pain, muscle weakness, flu symptoms, nausea and vomiting. Keywords: botulinum toxin; neuropathic pain; pain treatment; neuralgia; BoNT / A